Patient's experience with subcutaneous and oral methotrexate for the treatment of rheumatoid arthritis. Issue 1 (December 2016) - Curtis, J.; Xie, F.; Mackey, D.; Gerber, N.; Bharat, A.; Beukelman, T.; Saag, K.; Chen, L.; Nowell, B.; Ginsberg, S.
Abstract Background Despite the prominent position of methotrexate (MTX) in Rheumatoid Arthiris (RA) therapeutics, its real-world effectiveness may be influenced by a relative lack of tolerability or other side effects that physicians may not be aware of but that are bothersome to patients. The aim of this study is to identify suboptimal patient experience with MTX and to raise awareness for clinicians to identify opportunities to mitigate bothersome symptoms and side effects and optimize response to MTX. Methods We conducted a prospective, cross-sectional, online survey among RA patients who were members of Creakyjoints, a large arthritis patient community. Eligible participants must have recently initiated a new biologic, subcutaneous (SQ) MTX, or oral MTX in the last 12 months and were uniquely assigned to one of these 3 groups. Descriptive statistics were used to compare patient-reported side effects and tolerability related to MTX use in the 3 medication groups (SQ MTX, oral MTX, and biologic). Results A total of 382 (85 %) of 448 eligible patients completed the survey and were grouped as: biologic (n = 218), SQ MTX (n = 49), and oral MTX (n = 115). Demographics were mean standard deviation (SD) age 48 (10) years, 92 % white, 91 % women. Symptoms significantly more prevalent in the SQ and oral MTX groups included diarrhea, fatigue, malaise, and hair loss. Injection related pain was lower with SQ MTX compared to SQ biologics. Out of a total of 8 potential symptoms and side effects examined, higher dose MTX (> = 20 mg/week) was associated with a 2.26 (1.25–4.09) greater likelihood of more side effects referent to < =10 mg/week. Conclusion Results from this real-world RA patient cohort suggest that MTX is accompanied by many patient-reported side effects and tolerability problems that may be under-recognized by physicians. These may impact both treatment satisfaction and medication adherence.